Mengukur Kepuasan Mahasiswa Terhadap Kegiatan Akademik di Pendidikan Tinggi Islam - Fahrurrozi Fahrurrozi (EL-TARBAWI, 2014)
The current research aims at understandicng student satisfaction level on academic adminitration service of Kependidikan Islam (KI) study program, Faculty of Tarbiyah IAIN Walisongo Semarang. There are 83 respondents as research sample. Research analysis method used in this current study is importanceperformance analysis from John A. Martila and John C. James. The study result shows two findings: 1) level of student satisfaction on academic administration service, when expectation conform with implementation, is 62,69%; and 2) level of student satisfaction on lecture and instructor service is 66,03%.